2015
DOI: 10.1371/journal.pone.0140437
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Preexisting Interstitial Lung Disease on Acute, Extensive Radiation Pneumonitis: Retrospective Analysis of Patients with Lung Cancer

Abstract: IntroductionThis study investigated the clinical characteristics and predictive factors for developing acute extended radiation pneumonitis with a focus on the presence and radiological characteristics of preexisting interstitial lung disease.MethodsOf 1429 irradiations for lung cancer from May 2006 to August 2013, we reviewed 651 irradiations involving the lung field. The presence, compatibility with usual interstitial pneumonia, and occupying area of preexisting interstitial lung disease were retrospectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 32 publications
0
45
0
2
Order By: Relevance
“…164 Both chemotherapy and thoracic surgery can cause an acute exacerbation in ILD patients 167,168 and radiotherapy is associated with the risk of radiation pneumonitis. 164,169 The infectious complications of chemotherapy can also be challenging in patients who have required immunosuppression for their lung disease. Individualized diagnostic and management pathways are necessary for SSc-ILD patients who develop suspected/proven malignancy, with a patient-centered approach.…”
Section: Malignancy In Ssc-ildmentioning
confidence: 99%
“…164 Both chemotherapy and thoracic surgery can cause an acute exacerbation in ILD patients 167,168 and radiotherapy is associated with the risk of radiation pneumonitis. 164,169 The infectious complications of chemotherapy can also be challenging in patients who have required immunosuppression for their lung disease. Individualized diagnostic and management pathways are necessary for SSc-ILD patients who develop suspected/proven malignancy, with a patient-centered approach.…”
Section: Malignancy In Ssc-ildmentioning
confidence: 99%
“…The two patients with grade 5 PF were diagnosed with mild IP on diagnostic imaging. Ozawa et al investigated the clinical characteristics and predictive factors for developing acute extended RP with a focus on the presence and radiological characteristics of preexisting IP, and concluded that the presence of preexisting IP on the CT scan before radiotherapy was a significant predictive factor (odds ratio ¼ 22.6; 95% confidence interval: 5.29-155; p < .001) [24]. Lee et al reported that the interstitial changes in the pre-RT chest CT scan (p ¼ .009), mean lung dose (p < .001), and the percentage of lung volume receiving over 30 Gy (V30) (p < .001) significantly predicted RP on multivariate analysis.…”
Section: Grade 5 Pfmentioning
confidence: 99%
“…V různých studiích byl výskyt PP všech stupňů popsán až u 73 % ozářených nemocných s mediánem odstupu od SBRT 1,9 měsíce. Výskyt PP stupně 3 byl v 5, 3 % a byl častější, pokud se PP objevila do 1 měsíce od SBRT [8,9]. V jiné studii měl výskyt symptomatické PP medián 5 měsíců [10].…”
Section: Indikace Radikální Radioterapie Karcinomu Plic U Ipfunclassified
“…SBRT u IPF je i nadále považovaná za kontroverzní a v japonské prospektivní studii JCOG 0403 byla prokázaná IPF považovaná za relativní kontraindikaci SBRT [15]. Jsou popsány také případy vzniku závažné exacerbace subklinické IPF po SBRT při minimálních známkách předchozího intersticiálního postižení [9]. PP stupně 2 byla popsána až v 50 % případů u nemocných po SBRT, pokud byly před radioterapií prokázány jakékoli intersticiální změny na CT plic [16].…”
Section: Indikace Radikální Radioterapie Karcinomu Plic U Ipfunclassified